Sustainable Transportation in the Context of Indonesia Emas 2045: Facilitating the Transition Towards an Environmentally Friendly Future - Annisa, Annisa; Sutanto, Sutanto; Arief, Budi; Wiradinata, Irvan (Jurnal Daur Lingkungan, 2024)
Sustainable transportation plays a crucial role in realizing Indonesia's long-term vision for the year 2045, known as "Indonesia Emas 2045". The rapid economic growth experienced by Indonesia has led to urbanization and an increased demand for transportation services. However, this development has also brought adverse environmental impacts such as air pollution, traffic congestion, and greenhouse gas emissions. This study emphasizes the importance of public awareness and education in successfully achieving the sustainable transportation goals set for 2045. The methodology employed in this literature review aims to gain a comprehensive understanding of the impacts and solutions of sustainable transportation. Literature research findings indicate that public awareness and education play a crucial role in advocating for sustainable transportation alternatives. Increasing public awareness of the environmental, economic, and social benefits of sustainable transportation has the potential to drive the use of public transportation, non-motorized vehicles, and electric vehicles. The research confirms that public awareness efforts have been successful in reducing the use of private cars, promoting public transportation use, and fostering interest in non-motorized transportation. Additionally, these efforts have proven to increase support for sustainable transportation policies. Therefore, it is crucial to implement effective communication campaigns and education programs to assist individuals in making environmentally conscious transportation choices. In the context of "Indonesia Emas 2045," it is essential to enhance public awareness and ensure adequate education regarding sustainable transportation. Collective support from the community can significantly contribute to achieving sustainable development goals, propelling Indonesia towards a greener and more prosperous future.